2016
DOI: 10.1038/jp.2016.134
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of the efficacy of 4 weeks of supplementation with ω-3 polyunsaturated fatty acids in cases of unexplained oligohydramnios

Abstract: The results suggest that ω-3 fatty acids may have a role in the increase in AFI in cases of unexplained oligohydramnios. This effect may be secondary to the increase in uterine blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…According to a study conducted in Egypt in 2016, omega has successfully increased the amount of amniotic fluid in patients presenting unexplained oligohydramnios. The aforementioned study has also found reduced uterine artery resistance and pulsatility indices; this outcome suggested that the increased amniotic fluid was associated with improved uterine flow [21]. Other studies have also proved that omega improved uterine artery perfusion in non-pregnant patients [22].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to a study conducted in Egypt in 2016, omega has successfully increased the amount of amniotic fluid in patients presenting unexplained oligohydramnios. The aforementioned study has also found reduced uterine artery resistance and pulsatility indices; this outcome suggested that the increased amniotic fluid was associated with improved uterine flow [21]. Other studies have also proved that omega improved uterine artery perfusion in non-pregnant patients [22].…”
Section: Discussionmentioning
confidence: 77%
“…This outcome is encouraging and interesting because it allows reasoning about the role played by omega as antioxidant and in reducing inflammatory processes to facilitate placentation and to enable good placental flow for proper fetal growth [1,20]. Such omega performance has been investigated and cited in several studies [21][22][23]. According to a study conducted in Egypt in 2016, omega has successfully increased the amount of amniotic fluid in patients presenting unexplained oligohydramnios.…”
Section: Discussionmentioning
confidence: 93%
“…ОБЗОРЫ эффекты, связанные с приемом омега-3 ПНЖК во время беременности: увеличение объема околоплодных вод при маловодии [18]; эффективная профилактика депрессии во время беременности и после родов [19]; профилактика сниженной массы тела при рождении (в частности, крупномасштабное исследование 12 373 беременных показало, что низкие концентрации омега-3 ПНЖК в плазме крови были связаны с более низкой массой тела новорожденных (отношение шансов 1:4) [4]); снижение риска развития аллергий у детей [20] (например, пищевая аллергия на яйца встречалась только у 9% детей, рожденных от матерей, получавших 900 мг/сут омега-3 ПНЖК во время беременности, а в контроле -у 15% детей). Дети от матерей, получавших дотации омега-3 ПНЖК во время беременности, имели более высокую степень восприятия и воспроизведения речи по шкалам МакАртура и Бейли на 12, 14 и 18-й месяцы жизни [21].…”
Section: The Work Was Done Under Grant 16-07-01129 Of the Rfbrunclassified
“…The free radicals release during pregnancy impairs vascular endothelial function and subsequent vasoconstriction will occur [11] . Omega-3 fatty acids, as antioxidants, inhibit free radicals release; this leads to an increase in the blood flow to the uterus and placenta which may improve pregnancy outcomes [12] . The effectiveness of omega-3 fatty acids on the birth weight of IUGR was studied before with promising results [9] .…”
Section: Introductionmentioning
confidence: 99%